A Vision-Based Human Hand Gesture Recognition Interface For Image Browsing Application - Chan , Lih Yang (2009)
Computer mouse has been an efficient input device. However, the mouse usage limits user’s freedom. Besides, the devices are easily contaminated with bacteria and spreading disease among users. The contactless vision-based hand gesture recognition is one of the solutions to the freedom and hygiene problem. But it faces challenges of usability in term of cost and environmental variation like lighting. This thesis proposes and implements hand gesture recognition methods in image browsing application, to allow users views pictures contactless from input device in real time.